Understanding wellness and barriers to care among Iraqi refugee women in the United States. (23rd July 2019) - Ross Perfetti, Angela; Abboud, Sarah; Behme, Matthew; Barg, Frances K.
Abstract: Iraqi refugees in the US experience a high prevalence of non‐communicable diseases. In this article, we explore how cultural and structural realities intersect to influence utilisation of preventative healthcare and cancer screening with the aim of understanding health disparities in this population. We conducted three focus group discussions with a total of 14 Iraqi refugee women living in a northeastern US city in 2016 and analysed the qualitative data using a thematic analysis. Eight themes emerged from our data: (a) 'prevention is better than cure:' Iraqi refugee women maintain wellness; (b) physical and mental health are interrelated in causing and curing ill‐health; (c) Iraqi refugee women embrace both biomedical and other healing practices; (d) God contributes to healing; (e) cancer is caused by dangerous environments. Three of the eight themes related to barriers to care; (f) multi‐level problems within hospitals and clinics prevent the delivery of care; (g) financial barriers prevent access to care and good health; (h) competing priorities are a barrier to good health. We argue that understanding refugee health requires critical analysis of both culturally informed understandings of health and illness as well as the structural aspects of health disparities that result in limited access to life opportunities, racism and inequality for refugees and their communities.